Dissecting the Acid Stress Response of Rhizobium tropici CIAT 899 - Guerrero-Castro, Julio; Lozano, Luis; Sohlenkamp, Christian (Frontiers in Microbiology, 2018)
Rhizobium tropici CIAT899 is a nodule-forming α-proteobacterium displaying intrinsic resistance to several abiotic stress conditions such as low pH and high temperatures, which are common in tropical environments. It is a good competitor for Phaseolus vulgaris (common bean) nodule occupancy at low pH values, however little is known about the genetic and physiological basis of the tolerance to acidic conditions. To identify genes in R. tropici involved in pH stress response we combined two different approaches: (1) A Tn5 mutant library of R. tropici CIAT899 was screened and 26 acid-sensitive mutants were identified. For 17 of these mutants, the transposon insertion sites could be identified. (2) We also studied the transcriptomes of cells grown under different pH conditions using RNA-Seq. RNA was extracted from cells grown for several generations in minimal medium at 6.8 or 4.5 (adapted cells). In addition, we acid-shocked cells pre-grown at pH 6.8 for 45 minutes at pH 4.5. Of the 6289 protein-coding genes annotated in the genome of R. tropici CIAT 899, 383 were differentially expressed under acidic conditions (pH 4.5) versus control condition (pH 6.8). 351 genes were induced and 32 genes were repressed; only 11 genes were induced upon acid shock. The acid stress response of R. tropici CIAT899 is versatile: we found genes encoding response regulators and membrane transporters, enzymes involved in amino acid and carbohydrate metabolism and proton extrusion, in addition to several hypothetical genes. Our findings enhance our understanding of the core genes that are important during the acid stress response in R. tropici.